CURRENT CHALLENGES AND FUTURE DIRECTIONS IN STOMATOLOGY: A COMPREHENSIVE REVIEW - Xudoyberdiyeva Muslima Abdukaxorovna; Xabibova Nazira Nasullaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Stomatology, as a branch of dentistry and oral medicine, faces evolving challenges arising from epidemiologic transitions, technological innovations, and systemic health interconnections. This review aims to summarize key current issues in stomatology, analyze their underlying causes, and propose future directions.